“AJA RUMANGSA BISA NANGING BISAA RUMANGSA” PESAN MORAL DALAM KEARIFAN LOKAL JAWA MELALUI CERPEN “JENENGKU: ASU” KARYA KRISHNA MIHARJA - Yohanes Adhi Satiyoko (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
This research aims to reveal humanism in political field as portrayed through Javanese short story by Krishna Miharja entitled “Jenengku: Asu”. Problem formulation is how the dialectic of main character to his social life. The purpose of the research is explaining the main character to his social life, particularly to his own political ambition. The discussion in the analysis uses sociology of knowledge framework of Peter Berger through dialectic process of externalization, objectivation, and internalization. The result shows that the failure of main character in fulfilling his ambition is stimulated from his political ambition without sufficient ability and knowledge. That attitude is against the Javanese philosophy “aja rumangsa bisa, nanging bisaa rumangsa”, a local wisdom to self introspection.